1993
DOI: 10.1021/cm00033a027
|View full text |Cite
|
Sign up to set email alerts
|

Chemical vapor deposition of gallium sulfide: phase control by molecular design

Abstract: Gallium sulfide (Gas) thin films have been grown at 380-420 "C by atmospheric pressure metal-organic chemical vapor deposition (MOCVD) using the single-source precursors [ (tB~)2-Ga(StBu)]2, [ (tBu)GaS]4, and [(tBu)GaS17. Characterization of the films by X-ray photoelectron spectroscopy (XPS), Rutherford backscattering (RBS), and energy-dispersive X-ray (EDX) analysis shows all the films to be of chemical composition Ga:S (1:l). However, from transmission electron microscopy (TEM) and X-ray diffraction (XRD) t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
59
1

Year Published

1997
1997
2007
2007

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(60 citation statements)
references
References 0 publications
0
59
1
Order By: Relevance
“…Both the halite-type, and the zinc blendetype have cubic face-centered lattices, therefore they are difficult to distinguish on diffraction patterns, when preferred orientations may affect reflection intensities. It was not until a year after the first report that the authors discussed this point [107] and proposed the ª¼halite to zinc blende transformation be facile on the surface for the growing film¼º, and that ª¼during deposition on GaAs (100) the substrate surface will promote such a change¼º (GaAs is of the zinc blende-type). ªThus, while a cubic phase is determined by the precursor, its growth is enhanced by the cubic GaAs substrate.º The first experiments have shown that cubic GaS could be grown on a variety of substrates, including not only GaAs, but also borosilicate glass, Si, KBr, and Mo; [102] therefore the halite to zinc blende modification can occur without a zinc blende-type surface.…”
Section: From Alkyl Metal Chalcogenatesmentioning
confidence: 99%
See 1 more Smart Citation
“…Both the halite-type, and the zinc blendetype have cubic face-centered lattices, therefore they are difficult to distinguish on diffraction patterns, when preferred orientations may affect reflection intensities. It was not until a year after the first report that the authors discussed this point [107] and proposed the ª¼halite to zinc blende transformation be facile on the surface for the growing film¼º, and that ª¼during deposition on GaAs (100) the substrate surface will promote such a change¼º (GaAs is of the zinc blende-type). ªThus, while a cubic phase is determined by the precursor, its growth is enhanced by the cubic GaAs substrate.º The first experiments have shown that cubic GaS could be grown on a variety of substrates, including not only GaAs, but also borosilicate glass, Si, KBr, and Mo; [102] therefore the halite to zinc blende modification can occur without a zinc blende-type surface.…”
Section: From Alkyl Metal Chalcogenatesmentioning
confidence: 99%
“…In the same article, [107] the authors compare results obtained for the MOCVD of GaS from three structurally distinct precursors, dimeric [( t Bu) 2 Ga(l 2 -S t Bu)] 2 , tetrameric [( t Bu)Ga(l 3 -S)] 4 , and heptameric [( t Bu)Ga(l 3 -S)] 7 , in order to gain further insight into phase control by molecular design. As expected, [( t Bu)Ga(l 3 -S)] 4 yielded the cubic GaS phase, but in a narrow temperature window at about 400 C. At the same temperature, [( t Bu) 2 Ga(l 2 -S t Bu)] 2 yielded the thermodynamically stable GaS hexagonal phase as poorly crystallized films.…”
Section: From Alkyl Metal Chalcogenatesmentioning
confidence: 99%
“…Since the initial report by McInnes et al 1 concerning a metastable cubic form of GaS, a great deal of work has been devoted to such cubic phases [2][3][4][5][6][7][8] and their role in GaAs surface passivation, 2 and metal-oxide-semiconductor field-effect transistors 5 have been investigated. In most published reports cubic GaS thin films were prepared by metal-organic chemical vapor deposition using ͓͑t-Bu͒GaS͔ 4 cubane, 7 with the purpose of checking if the ͓GaS͔ 4 cubane units of the precursor molecule were preserved in the deposited thin film.…”
Section: Introductionmentioning
confidence: 99%
“…[4] Of course, the distinction between MBMs and MDMs is not absolute. The thermolysis of [Ga( t Bu) 2 S] 2 , for example, forms the well-known hexagonal GaS, while heating the cubane-structured [Ga( t Bu)S] 4 molecule between 380 and 400 C leads to cubic GaS, a new, metastable form of GaS, which forms the thermodynamically stable hexagonal form upon heating above 400 C. [5] Hence, cubic GaS might be termed an MBM, and hexagonal GaS an MDM. Other examples could be cited where a material can be made as either an MBM or MDM, or an MDM can be converted to an MBM, for example, via intercalation of a molecular component.…”
Section: Introductionmentioning
confidence: 99%